Perancangan Sistem Informasi Praktik Kerja Industri di Sekolah Menengah Kejuruan (SMK) Berbasis Website (Current Research in Education: Conference Series Journal, 2023)
In SMK there are industrial work practices activities, where these activities do not exist in SMA or its equivalent. The purpose of industrial work practices is to prepare vocational high school students to be able to adapt to the world of work they will face after graduating from school. However, in its implementation there are obstacles encountered such as manual data management and information delivery through teachers or bulletin boards. So that these obstacles cause spending to buy paper, the information obtained is limited and presented in poor condition, prone to errors when taking notes, ineffective and efficient. The purpose of this research is to design an industrial work practice information system that can integrate admins, teachers and students to make it easier to manage data, monitor, obtain information, provide reports and feedback. The data collection technique uses literature study, while the software development method uses Rapid Application Development. The results of this study present a prototype of a website-based Information System which is expected to facilitate the implementation of industrial work practices in vocational high schools.